HUBUNGAN INTENSITAS PERILAKU BERMAIN GAME ONLINE ARENA OF VALOR (AOV) DENGAN AKTIVITAS BELAJAR SISWA-SISWI SMP INSAN KAMIL BOGOR - Saliha, Nabila Wahyu; Kusumawardhani, Sarita; Magfira, Shailla Gafdi (Jurnal Vokasi Indonesia, 2021)
The presence of Arena of Valor (AOV) online games with interesting game features is popular entertainment in the community, especially among students. However, online gaming has both positive and negative impacts. The higher the intensity of a person's behavior playing online games can affect learning activities at school. Quantitative with a correlational approach will be used to determine the relationship between the behavior intensity of playing AOV online games with the learning activities of SMP Insan Kamil Bogor students. Both the cultivation theory and learning achievement theory will also be used in this research. Respondents in this study were the students of SMP Insan Kamil Bogor with the total of 780 people, this research is using a non- probability sampling technique, along the Slovin formula and finally distributed to 90 respondents. The results of this study indicate that the relationship between the intensity of AOV online game behavior and student learning activities is 0.486, which is indicating quite strong result. The implication of the research is expected to helping the maintenance of learning activities, by controlling the intensity of behavior playing online games through the help of educators, namely teachers and parents. Then, the next research is expected to use the topic of the problem from a different point of view and method.